Perbedaan Tingkat Kecerdasan Emosional Siswa Berdasarkan Kegiatan Ekstrakurikuler Olahraga Permainan - Dini Tresnadiani; Fibrianti Kusuma Wardani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to analyze the level of emotional intelligence of high school students who take extracurricular sports games based on the type of sport and gender. The research method used is descriptive quantitative survey techniques on 168 high school students who take part in sports game extracurricular activities. The results showed that there were no significant differences in the level of emotional intelligence of students who took part in extracurricular activities in individual and team sports, but based on gender there were significant differences in the level of emotional intelligence in students who took part in sports extracurricular activities in the Majalengka area. In conclusion, the level of emotional intelligence of students who take extracurricular sports games is included in the moderate category and there are no differences in students based on the type of sport. While based on gender there are differences in the level of emotional intelligence with female students having higher abilities than male students. Keywords: Emotional Intelligence, Students, Sports Games, Types of Sports